Selecting the Sustainable Tourist Market for Bali Based on Carbon Footprint - Anom Hery Suasapha; I Wayan Suardana; Putu Sucita Yanthy; I Nyoman Sunarta; Anderson Ngelambong (Universitas Udayana, 2025)
This article investigates the carbon footprints of tourists from various countries to inform Bali's sustainable tourism strategy, especially its environmental sustainability. Analysing data from the top 20 tourist-generating countries, the research employs a carbon footprint calculator to assess emissions associated with their flights. The findings categorise these countries into three groups based on their carbon emissions: low, medium, and high-carbon footprint markets. Countries with lower carbon footprints, particularly Southeast Asian ones, should be prioritised as target markets to promote sustainable tourism in Bali. Conversely, tourists from medium and high-carbon-footprint countries should be considered the less-preferred tourist market, and their number should be reduced through demarketing strategies. The article concludes with managerial implications and highlights research limitations, emphasising the need for ongoing efforts in sustainable tourism management.